Uji Daya Hambat Ekstrak Air Biji Kopi Arabika pada Kultur Bakteri MRSA - Daisy Grace Agustina; Hendro Sudjono Yuwono; Eka Hendryanny (Bandung Conference Series: Medical Science, 2024)
Abstract. The emergence of Methicillin-Resistant Staphylococcus aureus (MRSA) strains has led to the need for alternative treatments to natural products such as coffee. Arabica coffee contains chlorogenic acid and caffeic acid which play an antibacterial role against MRSA. Arabica coffee water extract also has antibacterial properties against S.aureus. This experimental research tested the inhibitory power of Arabica coffee bean water extract against MRSA bacteria. The method used was Kirby-Bauer disk diffusion with Arabica coffee bean water extract treatment groups of 100% and 50% concentration, vancomycin positive control and distilled water negative control. The research was carried out in the Microbiology Lab of FK Unpad from March to October 2023. The results of the antibacterial test showed that there was an inhibition zone in the Arabica coffee bean water extract with a concentration of 100% and 50% in the MRSA bacterial culture. The results of the inhibition zone diameter test for each concentration will be analyzed and explained descriptively. This can be concluded that there is an inhibitory effect of Arabica coffee bean water extract at concentrations of 100% and 50% on MRSA bacterial cultures. Abstrak. Munculnya strain resisten Methicillin-Resistant Staphylococcus aureus (MRSA) menyebabkan dibutuhkannya pengobatan alternatif produk alam seperti kopi. Kopi Arabika mengandung asam klorogenat dan asam kafeat yang berperan antibakteri terhadap MRSA. Ekstrak air kopi Arabika juga memiliki antibakteri terhadap S.aureus. Penelitian eksperimental ini menguji daya hambat ekstrak air biji kopi Arabika terhadap bakteri MRSA Metode yang digunakan adalah disk diffusion Kirby-Bauer dengan kelompok perlakuan ekstrak air biji kopi Arabika konsentrasi 100% dan 50%, kontrol positif vankomisin dan kontrol negatif aquades. Penelitian dilakukan di Lab Mikrobiologi FK Unpad bulan Maret hingga Oktober 2023. Hasil uji antibakteri menunjukkan adanya zona inhibisi pada ekstrak air biji kopi Arabika konsentrasi 100% dan 50% pada kultur bakteri MRSA. Hasil uji daya hambat diameter zona hambat dari masing-masing konsentrasi akan dianalisis dan dijelaskan secara deskriptif. Hal ini dapat disimpulkan terdapat daya hambat ekstrak air biji kopi Arabika pada konsentrasi 100% dan 50% pada kultur bakteri MRSA.